Using protection motivation theory to evaluate the impact of cybersecurity practices on user experience with e-commerce platforms among internet café users in Gqeberha - Obisesan, Segun Musa (https://orcid.org/0009-0008-9819-8794) (Rhodes University, 2026)
Online shopping has become deeply embedded in modern society, despite the growth of cybersecurity concerns linked with e-commerce platforms, particularly among users accessing public internet café through unsecured connections. Limited research has examined how cybersecurity practices affect e-commerce platform users ‘experiences in insecure public internet cafés. This study used the Protection Motivation Theory (PMT)to assess the impact of cybersecurity practices on the experiences of online shoppers with e-commerce platforms in Gqeberha. The study population consists of e-commerce platform users mainly online shoppers from the internet cafés, with purposive sampling used to select three busy internet cafés located at the centre of Gqeberha city. The study utilised explanatory sequential mixed-methods, using probability sampling to administer100 questionnaires and purposive sampling to select7 participants for in-depth interviews for both quantative and qualitative phases. Quantitative data were analysed using Statistical Package for the Social Sciences version 29with descriptive and inferential statistics, while qualitative data were thematically analysed using ATLAS.ti 25 following Braun and Clarke’s six-phase. The findings reveal high perceived severity and vulnerability regarding cybersecurity risks, such as phishing, smishing, and One-Time Password (OTP) attacks, which cause financial losses among e-commerce platform users in public internet cafés. Users' disregard for security practices led to negative experiences. E-commerce platform users with cybersecurity knowledge and shopping experiences demonstrated high self-efficacy and response efficacy in adopting cybersecurity practices, such astwo-factor authentication, password managers, verification processes, and virtual card payment, to prevent fraud while shopping in internet cafés. Security measures’ visibility on the e-commerce platforms improves user trust and self-efficacy. The study further concluded that a lack of cybersecurity knowledge led to low self-efficacy and response efficacy to follow security practices, making users vulnerable to online attacks and causing dissatisfaction. The study concluded that a lack of instructions and high perceived response costs, like inconvenience or time delay, were key challenges, affecting cybersecurity practices. The study recommended educating users on implementing security best practices such as using password managers, virtual cards and site verification. E-commerce platforms supported education is necessary to keep users informed about security measures, and biometric verification should be implemented on e-commerce platforms. This study was restricted by the sample size for both qualitative and quantitative phases, and the sites where it was conducted in Gqeberha. Further studies could explore PMT constructs and cybersecurity practices across other cities of the Eastern Cape and other South African provinces, expanding the geographical coverage.
Keywords: Behavioral cybersecurity (http://id.loc.gov/authorities/subjects/sh2023000800); Self-efficacy (http://id.loc.gov/authorities/subjects/sh93006407); Cybercafes -- South Africa -- Gqeberha (http://id.loc.gov/authorities/subjects/sh98003569); Information Systems; User experience (https://www.wikidata.org/wiki/Q1047808); E-commerce platform (https://www.wikidata.org/wiki/Q18450215)